Grouting material, prefabricated lightweight aggregate concrete and preparation method thereof

By using alkaline magnesium sulfate cement and polymer emulsion modified light coarse aggregate in prefabricated light aggregate concrete, the locking structure is formed, which solves the problems of low compressive and flexural strength, and achieves lightweight, high strength and high toughness concrete properties.

CN116891387BActive Publication Date: 2024-12-20WUHAN UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310810954.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2024-12-20
Estimated Expiration
2043-07-03

AI Technical Summary

Technical Problem

The existing prefabricated light aggregate concrete has low compressive and flexural strength, which limits its application scenarios.

Method used

Using alkaline magnesium sulfate cement as grouting material, combined with polymer emulsion modified light coarse aggregate, the whisker-like hydration product of alkaline magnesium sulfate cement forms a lock structure with porous light coarse aggregate to enhance the concrete resistance Fold strength and toughness, and reduce grout density through fly ash and glass beads to improve fluidity.

Benefits of technology

It significantly improves the flexural strength and toughness of lightweight high-strength high-tough concrete, reduces its own weight, and reduces the shrinkage of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116891387B_ABST
    Figure CN116891387B_ABST
Patent Text Reader

Abstract

The present invention discloses a grouting material, a prefabricated lightweight aggregate concrete and a preparation method thereof. The grouting material, by weight, comprises raw materials including: 210-240 parts of basic magnesium sulfate cement, 75-95 parts of silica fume, 20-35 parts of glass microspheres, 50-70 parts of fly ash, 150-180 parts of lightweight pottery sand, 50-70 parts of water, and 10-20 parts of water reducer. The present invention uses a crushed stone type shale lightweight aggregate modified by a polymer emulsion as an interlocking skeleton and reduces the density; basic magnesium sulfate cement is used to replace ordinary silicate cement to prepare a grouting material, and the basic magnesium sulfate cement whisker-like hydration product 5·1·7 phase is further interlocked with a porous light coarse aggregate, and at the same time, the porous light coarse aggregate releases the polymer emulsion to toughen the surrounding structure of the aggregate, and synergistically improves the flexural strength and toughness of the concrete. The lightweight, high-strength, and high-toughness concrete prepared by the present invention has the advantages of low deadweight, high flexural strength, and good toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, in particular to a grouting material, a prefabricated lightweight aggregate concrete and a preparation method thereof. Background Art

[0002] Lightweight aggregate concrete has significant technical advantages in applications such as long-span bridges, high-rise buildings, and harsh environment structural engineering due to its advantages such as light weight, high strength, and good durability. However, due to the problems of lightweight aggregate being light and porous and having low strength, the amount of cement required to prepare lightweight aggregate concrete is large, and lightweight aggregate is easy to float and shrink, and the strength and density levels are difficult to improve. These problems have limited the application scenarios of lightweight aggregate concrete.

[0003] Chinese patent 202211113497.9 discloses a high-strength lightweight aggregate concrete and a preparation method thereof. The patent proposes to pre-immerse lightweight aggregate in an impregnation liquid composed of nanocellulose, fly ash, ultrafine silicate cement, a water reducer and an expansion agent to improve the strength of lightweight aggregate, reduce water absorption, and use the fine fibers formed by nanocellulose to adhere to the surrounding aggregates to prevent floating; the expansion agent is used to ensure the volume stability of the pores inside the lightweight aggregate. Chinese invention patent 202110091477.5 discloses a lightweight aggregate concrete and a preparation method thereof. The patent proposes to use fine ceramic powder and thickener to increase the viscosity of the slurry, reinforce the fiber to limit the movement of the aggregate, and inhibit the floating of the aggregate. It can be seen that the existing technology mainly obtains lightweight aggregates with high strength and good homogeneity by increasing the viscosity of the slurry or by aggregate processing, but the improvement of lightweight and high strength is limited, and due to the low strength of the lightweight aggregate itself, the bending and shearing properties are poor when it is damaged by load, and the brittleness is large.

[0004] Prefabricated lightweight aggregate concrete is a concrete that uses light coarse aggregate as a skeleton before pouring in high-fluidity cement paste. As the volume occupied by light coarse aggregate increases, the aggregates interlock with each other, and the amount of cement is reduced, the density of concrete can be effectively reduced, the floating of aggregates can be restricted, and the volume shrinkage can be reduced. However, since light coarse aggregate is used as a skeleton to bear the load, its low strength disadvantage is further magnified, resulting in relatively low compressive and flexural strengths of existing prefabricated lightweight aggregate concrete. At the same time, the prefabricated lightweight aggregate concrete technology requires the cement grouting material to be lightweight, high-strength, and high-fluidity. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical deficiencies, propose a grouting material, a prefabricated lightweight aggregate concrete and a preparation method thereof, and solve the technical problem of low compressive and flexural strength of prefabricated lightweight aggregate concrete in the prior art.

[0006] In a first aspect, the present invention provides a grouting material, wherein the raw materials thereof include, by weight: 210-240 parts of basic magnesium sulfate cement, 75-95 parts of silica fume, 20-35 parts of glass beads, 50-70 parts of fly ash, 150-180 parts of lightweight ceramic sand, 50-70 parts of water, and 10-20 parts of a water reducing agent.

[0007] In a second aspect, the present invention provides a method for preparing prefabricated lightweight aggregate concrete, comprising the following steps:

[0008] A grouting material and a polymer emulsion-modified light coarse aggregate are provided; wherein the grouting material is the grouting material provided in the first aspect of the present invention;

[0009] Aggregate pre-stacking: polymer emulsion modified light coarse aggregate is stacked in a mold and compacted to form a densely packed light coarse aggregate;

[0010] Grouting and curing: Pour the grouting material into tightly packed light coarse aggregate and obtain precast light aggregate concrete after curing.

[0011] In a third aspect, the present invention provides a precast lightweight aggregate concrete, which is obtained by the preparation method of the precast lightweight aggregate concrete provided by the second aspect of the present invention.

[0012] Compared with the prior art, the beneficial effects of the present invention include:

[0013] The present invention uses polymer emulsion-modified crushed stone shale lightweight aggregate as an interlocking skeleton and reduces the density; uses basic magnesium sulfate cement to replace ordinary silicate cement to make grouting material, and uses the basic magnesium sulfate cement whisker-like hydration product 5·1·7 phase to further interlock with porous lightweight coarse aggregate. At the same time, the porous lightweight coarse aggregate releases polymer emulsion to toughen the surrounding structure of the aggregate, and synergistically improves the flexural strength and toughness of the concrete. The lightweight, high-strength, and high-toughness concrete prepared by the present invention has the advantages of low deadweight, high flexural strength, and good toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is an electron microscope image of the internal pores of the aggregate in the prefabricated lightweight aggregate concrete provided in Example 2 of the present invention; in the image, the rod-like structure is the 5·1·7 phase. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0016] The present invention selects basic magnesium sulfate cement as the main cementitious material. Basic magnesium sulfate cement (BMSC) is a new type of magnesium cementitious material prepared by reasonable mixing ratio design of active magnesium oxide, magnesium sulfate heptahydrate and admixtures, and has the advantages of light weight, high strength, high bending resistance, high toughness, and not easy to rust steel bars. In particular, its main hydration product 5Mg(OH)2·MgSO4·7H2O (referred to as 5·1·7 phase) is whisker-shaped, and its bending strength can reach 2 to 3 times that of the same grade of silicate cement.

[0017] The present invention utilizes the porous characteristics of light coarse aggregate, first pre-absorbs polymer emulsion, then induces the nano-scale 5·1·7 phase to grow inside the porous light coarse aggregate, so that it is compounded with the polymer emulsion to form a network structure, further forming an interlocking structure, improving the brittleness of the aggregate, and improving the flexural strength and toughness of the concrete. At the same time, the light coarse aggregate absorbs and releases water to release water to cure the base grouting material, further reducing shrinkage.

[0018] The present invention partially replaces cement with fly ash and glass beads, which can not only reduce the density of the grouting material, but also has a spherical shape, which can improve the fluidity of the grouting material. However, the dosage of the two should not be too high, otherwise it will lead to a decrease in fluidity. The addition of lightweight pottery sand can not only reduce the density of the grouting material, but also further play the role of internal curing to reduce shrinkage.

[0019] Based on the above-mentioned inventive ideas, the detailed technical solution of the patent of this invention is as follows.

[0020] In a first aspect, the present invention provides a grouting material, wherein the raw materials thereof include, by weight: 210-240 parts of basic magnesium sulfate cement, 75-95 parts of silica fume, 20-35 parts of glass beads, 50-70 parts of fly ash, 150-180 parts of lightweight ceramic sand, 50-70 parts of water, and 10-20 parts of a water reducing agent.

[0021] In this embodiment, the active MgO and MgSO4·7H2O in the basic magnesium sulfate cement are compounded in a molar ratio of (8-9):1; the admixture is citric acid, and the admixture amount is 1-4% of the mass of the active MgO.

[0022] In this embodiment, the lightweight ceramic sand is obtained by crushing 500-grade shale ceramsite and sieving to ensure that its particle size is less than 0.5 mm; the apparent density of the glass microspheres is 0.20-0.25 g / cm 3 The present invention is based on the principle of the most dense packing, and optimizes the particle size and mass proportion of each cementitious material to make it have the most dense packing structure, thereby improving the strength of the grouting material and further improving the strength of the concrete.

[0023] In this embodiment, the water reducing agent is a polycarboxylate water reducing agent. Further, the polycarboxylate water reducing agent has a mass solid content of 25-30% and a water reduction rate of 30-35%.

[0024] In this embodiment, the raw materials of the grouting material include, by weight: 220-230 parts of basic magnesium sulfate cement, 85-90 parts of silica fume, 25-30 parts of glass beads, 65-70 parts of fly ash, 160-170 parts of lightweight ceramic sand, 60-65 parts of water, and 15-20 parts of water reducer.

[0025] In this embodiment, the grouting material is obtained by uniformly mixing basic magnesium sulfate cement, silica fume, glass beads, fly ash, lightweight ceramic sand, water, and a water reducing agent.

[0026] In this embodiment, the process of uniformly mixing basic magnesium sulfate cement, silica fume, glass beads, fly ash, lightweight ceramic sand, water, and water reducing agent comprises:

[0027] Mix basic magnesium sulfate cement, silica fume, glass beads and fly ash and stir evenly to obtain a mixed dry powder; wherein the stirring time is 0.5-2 minutes;

[0028] Add water and water reducing agent to the mixed dry powder, stir evenly to obtain mixed wet material; wherein the stirring time is 0.5-2min;

[0029] Add light ceramic sand to the mixed wet material, stir evenly, and obtain grouting material; the stirring time is 3-5 minutes.

[0030] In a second aspect, the present invention provides a method for preparing prefabricated lightweight aggregate concrete, comprising the following steps:

[0031] S1. providing grouting material and polymer emulsion-modified light coarse aggregate; wherein the grouting material is the grouting material provided by the first aspect of the present invention;

[0032] S2. Aggregate pre-stacking: polymer emulsion modified light coarse aggregate is stacked in a mold, and compacted to form a densely packed light coarse aggregate;

[0033] S3. Grouting and curing: Pour the grouting material into the tightly packed light coarse aggregate, and obtain the precast light aggregate concrete after curing.

[0034] In this embodiment, the polymer emulsion includes but is not limited to styrene-acrylic emulsion, styrene-butadiene emulsion, acrylic emulsion and other water-based polymer emulsions. Furthermore, the mass solid content of the polymer emulsion is 10-30%.

[0035] In this embodiment, the polymer emulsion modified light coarse aggregate is obtained by fully soaking the light coarse aggregate in the polymer emulsion and then filtering out the excess emulsion.

[0036] Among them, the light coarse aggregate is shale coarse aggregate with a particle size of 5-16mm and a bulk density of 700-900.

[0037] The soaking time is more than 12 hours, and further 24 hours.

[0038] The mixture may be stirred at intervals during the soaking process.

[0039] In this embodiment, the curing method is: after standard curing for 12-24 hours, the mold is taken out and demoulded, and standard curing is continued until the specified age.

[0040] In a third aspect, the present invention provides a precast lightweight aggregate concrete, which is obtained by the preparation method of the precast lightweight aggregate concrete provided by the second aspect of the present invention.

[0041] To avoid redundant description, some raw materials in the following embodiments and comparative examples of the present invention are summarized as follows:

[0042] The active MgO and MgSO4·7H2O in the basic magnesium sulfate cement are compounded in a molar ratio of 8.5:1; the admixture is citric acid produced by Sinopharm Group, and the admixture is 2% of the mass of the active MgO;

[0043] Lightweight ceramic sand is obtained by crushing and screening 500-grade shale ceramsite to ensure that its particle size is less than 0.5mm;

[0044] The apparent density of glass beads is 0.23g / cm 3 ;

[0045] The water reducer is a polycarboxylate water reducer with a solid content of 30% by mass;

[0046] The light coarse aggregate is a crushed stone type shale coarse aggregate with a particle size of 5-16mm and a bulk density of 900.

[0047] Example 1 Preferred grouting material

[0048] (1) Pour the weighed basic magnesium sulfate cement, silica fume, glass beads and fly ash into a mixing pot according to the proportion in Table 1 and dry mix for 1 minute;

[0049] (2) Add water and water reducing agent into a stirring pot and stir for 1 minute;

[0050] (3) Add light ceramic sand into the stirring pot and stir for 4 minutes to obtain grouting material.

[0051] The performance tests were performed on each grouting material in Example 1, and the results are shown in Table 2. The compressive strength was determined according to the national standard GBT17671-1999 cement mortar strength test method (ISO method); the fluidity was determined according to the GBT2419-2005 cement mortar fluidity determination method; and the V funnel time was determined according to the fluidity test method in QCR 409-2017 Technical Conditions for Grouting of Railway Post-Tensioned Prestressed Concrete Beam Pipelines.

[0052] Table 1 Raw materials and contents of grouting materials (parts by mass)

[0053]

[0054] (The amount of each raw material is based on 1m 3 According to the cement concrete mix design criteria, the amount of auxiliary cementitious materials such as fly ash and glass beads is calculated based on the volume replacement of cement. Therefore, when the mass of auxiliary cementitious materials is reduced or increased, the amount of cement will change accordingly.

[0055] Table 2 Compressive strength and fluidity of different grouting materials in Example 1

[0056]

[0057] As shown in Table 2, too high or too low content of glass beads and fly ash is not conducive to improving the compressive strength and fluidity of the grouting material, and the grouting material of Group 1 has the highest strength and the best fluidity. For the preparation of precast lightweight aggregate concrete, the fluidity of the grouting material is required to be high. According to the standard ACI 304.1R-92, the best fluidity is 18-26s, and only Group 1 can meet the requirements. Therefore, the optimal content range of fly ash and glass beads is determined.

[0058] Example 2

[0059] (1) Using the grouting material in Group 1 of Example 1 as the grouting material for prefabricated lightweight aggregate concrete;

[0060] (2) Modification of light coarse aggregate: Place the light coarse aggregate in a styrene-acrylic emulsion with a solid content of 20% by mass, stir it at intervals and soak it for 24 hours, then filter out the excess emulsion;

[0061] (3) Aggregate pre-stacking: The modified light coarse aggregate is stacked in a mold and compacted by a vibration table;

[0062] (4) Grouting and curing: Pour the grouting material into the tightly packed light coarse aggregate until the slurry is flush with the mold, scrape off the excess slurry on the surface, cover with plastic wrap, and after standard curing for 24 hours, take out the mold and demould it. Continue standard curing for 28 days to obtain precast light aggregate concrete.

[0063] In this embodiment, the volume proportion of light coarse aggregate in the concrete is about 60%.

[0064] Example 3

[0065] The difference between this embodiment and embodiment 2 is that the light coarse aggregate is modified by using acrylic emulsion with a solid content of 20% by mass.

[0066] Comparative Example 1

[0067] The difference from Example 2 is that the molding method is different. This comparative example adopts cast-in-place molding. The specific molding method is as follows: weigh the raw materials according to the following mass fractions: 340 parts of basic magnesium sulfate cement, 135 parts of silica fume, 40 parts of glass beads, 100 parts of fly ash, 250 parts of lightweight pottery sand, 670 parts of modified light coarse aggregate, 95 parts of water, and 22 parts of water reducer; pour the weighed powder and aggregate into a horizontal mixer, stir for 1 minute to mix them evenly, then pour water and water reducer and stir for 3 minutes, pour it into the mold, place it on a vibration table and vibrate it to make it dense, scrape off the excess slurry on the surface, cover it with plastic wrap, and after 24 hours of standard curing, take out the mold and demould it, and continue standard curing for 28 days to obtain lightweight aggregate concrete. It should be noted that in order to ensure the working performance of the cast-in-place molding technology, the maximum volume fraction of coarse aggregate can only be 40%, so the variables here are only the amount of glue and the volume proportion of aggregate, and the others are the same.

[0068] Comparative Example 2

[0069] The difference from Example 2 is that the light coarse aggregate is not modified by polymer emulsion.

[0070] Comparative Example 3

[0071] The difference from Example 2 is that the cement used is ordinary Portland cement P·O 52.5.

[0072] Comparative Example 4

[0073] The difference from Comparative Example 1 is that the cement used is ordinary Portland cement P·O 52.5.

[0074] The concrete of Examples 2 to 3 and Comparative Examples 1 to 4 was subjected to performance tests, and the test results are shown in Table 3. The compressive strength and flexural strength test standards are GBT 50081-2002 Standard for Mechanical Properties of Ordinary Concrete; the apparent density test method is JGJT12-2019 Technical Standard for Application of Lightweight Aggregate Concrete.

[0075] Table 3 Preparation process and performance comparison of concrete of Examples 2 to 3 and Comparative Examples 1 to 4

[0076]

[0077] Generally speaking, due to the high brittleness and low strength of light coarse aggregate, the higher the proportion of light coarse aggregate in the concrete system, the lower the strength of the concrete. However, since the nanoscale 5·1·7 phase, a whisker-like hydration product of basic magnesium sulfate cement, grows inside the porous light coarse aggregate and forms a composite network structure with the polymer emulsion, it is beneficial to improve the strength of the light coarse aggregate. At this time, increasing the proportion of light coarse aggregate does not necessarily lead to a decrease in concrete strength, and may even increase it. As shown in Table 3, compared with Comparative Example 1, Examples 2 to 3 use more modified light coarse aggregate, but due to the modification of the light coarse aggregate by the nanoscale 5·1·7 phase and the polymer emulsion, the compressive strength and flexural strength of the concrete can be significantly improved while reducing the density of the concrete. Compared with Examples 2 to 3, Comparative Example 2 did not use a polymer emulsion to modify the light coarse aggregate, resulting in the inability to polymerize with the nanoscale 5.1.7 phase to form a network structure, thereby failing to further improve the aggregate strength, which is manifested in the macroscopic view that the compressive and flexural strengths of the concrete are both low. At the same time, compared with Example 2, ordinary Portland cement is used in Comparative Example 3, which cannot form 5·1·7 phase to improve aggregate strength, resulting in extremely low compressive strength and flexural strength of concrete. In addition, by comparing Comparative Examples 3 and 4, it can be seen that when ordinary Portland cement is used, although the polymer emulsion has a certain strengthening and toughening effect on the light coarse aggregate, it is impossible to induce the nano-scale 5·1·7 phase to grow inside the porous light coarse aggregate, and the light coarse aggregate itself is still brittle. When preparing high-strength concrete (LC60), the amount of modified light coarse aggregate in Comparative Example 3 is more, but the concrete strength is also lower, which also illustrates the important role of basic magnesium sulfate cement in the present application system.

[0078] In order to further confirm the role of basic magnesium sulfate cement in prefabricated lightweight aggregate concrete system, SEM test was carried out on the aggregate in the prefabricated lightweight aggregate concrete provided in Example 2. Figure 1 ,from Figure 1 It can be seen that the pores inside the aggregate are filled with nano-rod-shaped 5·1·7 phase, which further verifies that the present invention improves the shortcomings of low strength and high brittleness of the aggregate by inducing the nano-scale 5·1·7 phase into the internal pores of the lightweight coarse aggregate, thereby ultimately improving the strength of precast lightweight aggregate concrete.

[0079] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing prefabricated lightweight aggregate concrete, characterized in that: The following steps are involved: Provide grouting materials and polymer emulsion modified light coarse aggregate; The polymer emulsion modified light coarse aggregate is piled in a mold, and compacted to form a densely packed light coarse aggregate; The grouting material is poured into the tightly packed light coarse aggregate, and after curing, a prefabricated light aggregate concrete is obtained; The specific components of the grouting material are as follows: by weight, the raw materials include: 210-240 parts of basic magnesium sulfate cement, 75-95 parts of silica fume, 20-35 parts of glass beads, 50-70 parts of fly ash, 150-180 parts of lightweight ceramic sand, 50-70 parts of water, and 10-20 parts of water reducer. In the basic magnesium sulfate cement, the molar ratio of active MgO to MgSO4·7H2O is (8-9): 1, the admixture is citric acid, and the admixture is 1-4% of the mass of active MgO. The lightweight ceramic sand is obtained by crushing 500-grade shale ceramsite and sieving to ensure that its particle size is less than 0.5 mm; the apparent density of the glass beads is 0.20-0.25 g / cm 3 ; The water reducer is a polycarboxylic acid water reducer.

2. The method for preparing prefabricated lightweight aggregate concrete according to claim 1, characterized in that: The grouting material comprises, by weight, 220-230 parts of basic magnesium sulfate cement, 85-90 parts of silica fume, 25-30 parts of glass beads, 65-70 parts of fly ash, 160-170 parts of lightweight ceramic sand, 60-65 parts of water, and 15-20 parts of water reducing agent.

3. The method for preparing prefabricated lightweight aggregate concrete according to claim 1, characterized in that: The polymer emulsion is at least one of styrene-acrylic emulsion, styrene-butadiene emulsion and acrylic emulsion.

4. The method for preparing prefabricated lightweight aggregate concrete according to claim 1, characterized in that: The polymer emulsion modified light coarse aggregate is obtained by fully soaking the light coarse aggregate in the polymer emulsion and then filtering out the excess emulsion.

5. The method for preparing prefabricated lightweight aggregate concrete according to claim 3, characterized in that: The light coarse aggregate is shale coarse aggregate with a particle size of 5-16 mm and a bulk density of 700-900; the soaking time is more than 12 hours.

6. The method for preparing prefabricated lightweight aggregate concrete according to claim 4, characterized in that: The curing method is: after standard curing for 12-24 hours, the mold is taken out and demoulded, and standard curing is continued until the specified age.

7. A prefabricated lightweight aggregate concrete, characterized in that: The prefabricated lightweight aggregate concrete is obtained by the preparation method of the prefabricated lightweight aggregate concrete according to any one of claims 1 to 6.